2011
DOI: 10.4103/0970-9290.84299
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat shock protein70 in oral submucous fibrosis and oral squamous cell carcinoma: An immunohistochemical study

Abstract: HSP70 is synthesized upon stress situations arising in cells of all living organisms. Expression of HSP70 indicates that stress plays an important role as a predisposing factor in oral submucous fibrosis and its subsequent progression to oral squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…On one hand, its high expression has been demonstrated in malignant tumors such as breast cancer [27], lung cancer [28], oral squamous cell carcinoma [29] and prostate cancer [30]; and moreover, its overexpression has been correlated with poor prognosis and resistance to therapy [27-30]. These suggest that Hsp70 might promote somehow tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, its high expression has been demonstrated in malignant tumors such as breast cancer [27], lung cancer [28], oral squamous cell carcinoma [29] and prostate cancer [30]; and moreover, its overexpression has been correlated with poor prognosis and resistance to therapy [27-30]. These suggest that Hsp70 might promote somehow tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…35 A significant increase in expression of Hsp-70 was observed where the tissue progressed from oral submucous fibrosis toward oral squamous cell carcinoma; it indicates that stress plays an important role as a predisposing factor for oral submucous fibrosis and its subsequent progression to oral squamous cell carcinoma. 36 By proteomic expression profile in our case, Hsp-70 1B was significantly increased in the OSMF tissues than the control. It is known that areca nut has a high copper content and generate reactives oxygen species during chewing.…”
Section: Discussionmentioning
confidence: 48%
“…Increased expression of HSP 70 was noted in leukoplakia with dysplasia and OSCC, suggested to be a marker for epithelial malignancy [52]. A study done on HSP 70 by Thubashini et al (2011) on OSMF and OSCC using IHC showed increased expression, attributed to increased copper levels, leading to elevated oxidative stress levels in OSMF [53]. A similar significant correlation has been observed in leukoplakia and OSCC compared to normal, and hence, the authors have concluded to explore more on the therapeutic approach for OPMD and OSCC [54].…”
Section: Discussionmentioning
confidence: 99%